Penetrating Abdominal Trauma from Liposuction: The Miami Experience - Nicole B. Lyons; Walter A. Ramsey; Brianna L. Cohen; Christopher F. O’Neil; Cristina Botero-Fonnegra; Carlos T. Huerta; Aris Arakelians; Sinan Jabori; Kenneth G. Proctor; Wrood Kassira; Joyce I. Kaufman; Edward B. Lineen; et al. (Trauma Care, 2023)
Liposuction is one of the most commonly performed aesthetic plastic surgery procedures in the world. Although serious complications are rare, intra-abdominal complications such as bowel perforation are one of the most common causes of death after liposuction. We present a case series of six patients who sustained intra-abdominal injuries from liposuction. The acute care surgery (ACS) faculty at a single institution were surveyed for patients. Six patients were identified over a three-year period. The average age was 45 years, and all patients were female. All six underwent a cosmetic procedure in addition to their liposuction. Four (67%) had previous abdominal surgery, and five (83%) were overweight or obese. All patients presented with abdominal pain, tachycardia, and leukocytosis. All six underwent exploratory laparotomies: four patients had small bowel enterotomies, one had cecal volvulus and abdominal compartment syndrome, and one had fascial violation. They underwent an average of four ACS procedures (range 1 to 11) and had an average hospital LOS of 29 days (range 5 to 60) and an average ICU LOS of 11 days (range 1 to 39). Intra-abdominal injuries are a rare complication of liposuction; however, a high index of suspicion must be maintained to diagnose and treat these life-threatening injuries.